Nowcasting GDP and inflation: the real-time informational content of macroeconomic data releases - Domenico Giannone; Lucrezia Reichlin; David H. Small (European Central Bank (ECB), 2006)
This paper formalizes the process of updating the nowcast and forecast on output and inflation as new releases of data become available. The marginal contribution of a particular release for the value of the signal and its precision is evaluated by computing "news" on the basis of an evolving conditioning information set. The marginal contribution is then split into what is due to timeliness of information and what is due to economic content. We find that the Federal Reserve Bank of Philadelphia surveys have a large marginal impact on the nowcast of both inflation variables and real variables and this effect is larger than that of the Employment Report. When we control for timeliness of the releases, the effect of hard data becomes sizeable. Prices and quantities affect the precision of the estimates of inflation while GDP is only affected by real variables and interest rates.
Keywords: E52; C33; C53; 330; factor model; forecasting; Large Data Sets; monetary policy; news; Real Time Data; Bruttoinlandsprodukt; Inflation; Messung; Prognoseverfahren; Geldpolitik; Schätzung; USA